Medical management of osteoarthritis during the COVID-19 pandemic: a challenge for the present and the future - Bernetti, A.; Farì, G.; Mangone, M.; Fiore, P.; Santilli, V.; Paoloni, M.; Agostini, F. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
The ongoing Covid-19 pandemic has inevitably changed the treatment of many chronic diseases which has been suspended or has suffered dangerous slowdowns. Osteoarthritis (OA) is the most common musculoskeletal disease. As a result, the medical management of Osteoarthritis was heavily impacted by the pandemic, and it required new therapeutic strategies. The purpose of this descriptive review is to provide an overview of how much the pandemic has affected the medical management of osteoarthritis and to outline a number of possible countermeasures. The COVID-19 pandemic requires a “multimodal approach”: physicians are called to test the management of Osteoarthritis patients at a distance, through the tools made available by telemedicine, for all cases in which direct contact is avoidable. Therapies that instead require a direct intervention on the patient impose that all the procedures are carried out in complete safety, scrupulously keeping to the use of personal protective equipements.